Catastrophic Health Expenditure Among Iranian Rural and Urban Households, 2013 - 2014 - Ghiasvand, Hesam (Iran Red Crescent Med J, 2015)
BACKGROUND: During the last two decades, the trend of out-of-pocket payments (OOP) for health services by Iranian households has been a matter of concern and it has exposed a significant proportion of them to catastrophic and impoverishing health expenditures. OBJECTIVES: The current study aimed to investigate three objectives: First, the mean of out-of-pocket payments among Iranian households for health services; second, the headcount and overshoot measures of catastrophic health expenditure; and finally the level of inequality in its distribution. MATERIALS AND METHODS: This descriptive study on Iranian rural and urban households was conducted from April to June 2015. The sample sizes were 19437 rural and 18888 urban households that Iranian Statistical Centre (ISC) selected them through a three -step randomized clustered sampling. The headcount and overshoot measures for catastrophic health expenditure were calculated. Also, the concentration index was calculated in order to investigate the inequality in distribution of the mentioned measures. RESULTS: The catastrophic health expenditure headcount ratio varied from 0.5% to 14.3% and from 0.48% to 13.27% for rural and urban households, respectively. Also, the overshoot of catastrophic health expenditure varied from 9.62% to 18.72% and from 8.8% to 17.74% for rural and urban households, respectively. CONCLUSIONS: Considering Iran’s economic condition during the last five years, the catastrophic health expenditure headcount ratio was more than 2% in Iran.